Bonded body, ceramic circuit board, semiconductor device, and bonded

By controlling the components and diffusion amount of Ag, Cu, active metal, Sn or In in the bonding layer of the ceramic copper circuit substrate, the problem of conductivity deviation of copper plates is solved, the bonding strength and heat dissipation are improved, and the ceramic circuit substrate is enhanced. Overall performance.

CN119403774APending Publication Date: 2025-02-07SPECIAL CERAMIC MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380048364.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-05
Filing Date
2023-06-27
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In ceramic copper circuit substrates, there is a local deviation in the conductivity in the copper plate, resulting in poor resistance and heat dissipation, affecting the performance of semiconductor components.

Method used

By adding elements such as Ag, Cu, active metal, Sn or In to the bonding layer between the ceramic substrate and the copper plate, the composition and diffusion of the bonding layer are controlled, ensuring that the detection amount of Cu is more than 80%, and limiting it in specific measurement points The detection amount of the first element is between 0 and 0.4 with respect to the detection amount of Ag.

Benefits of technology

The generation of AgSn alloy and AgIn alloy is effectively suppressed, conductivity deviation is avoided, bonding strength and heat dissipation are improved, and the overall performance of the ceramic circuit substrate is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403774A_ABST
    Figure CN119403774A_ABST
Patent Text Reader

Abstract

The present invention provides a ceramic circuit board capable of suppressing a decrease in the conductivity of a copper plate while maintaining the bonding strength. A bonded body according to an embodiment is provided with a ceramic substrate, a copper plate, and a bonding layer that bonds the ceramic substrate and the copper plate. The bonding layer contains Ag, Cu, an active metal, and a first element. The first element is one or two elements selected from the group consisting of Sn and In. When an arbitrary cross-section is analyzed by SEM-EDX, when the detection amount of Cu is 80% by mass or more and the slope change in a graph of the detection amount of Cu is the largest as a first measurement point, at the first measurement point, the detection amount (mass%) of the first element / the detection amount (mass%) of Ag is within the range of 0-0.4. It is preferable that the amount of detection (mass%) of the first element / the amount of detection (mass%) of Ag at the first measurement point be within the range of 0.05-0.2 (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments described below generally relate to a bonded body, a ceramic circuit substrate, a semiconductor device, and a method for manufacturing a bonded body. Background Art

[0002] The joint body of a ceramic substrate and a copper plate has been used as a circuit substrate for carrying semiconductor elements and the like. International Publication No. 2017 / 056360 (Patent Document 1) discloses a ceramic copper circuit substrate formed by joining a ceramic substrate and a copper plate. In Patent Document 1, the hardness and size of the exposed portion of the joining layer are controlled. In addition, in International Publication No. 2018 / 199060 (Patent Document 2), the diffusion area of ​​Ag into the copper plate is controlled.

[0003] The ceramic circuit substrates of Patent Document 1 and Patent Document 2 have excellent TCT (heat cycle resistance) characteristics. As semiconductor elements become more high-performance, the operating guaranteed temperature is expected to reach above 170°C and further reach above 200°C. In addition, the miniaturization of semiconductor devices equipped with semiconductor elements is also under study. Power density has always been used as a performance evaluation of semiconductor devices. Power density can be calculated by "power density = (rated current × rated voltage × number of semiconductor elements mounted on the module) / volume of the module". For example, the power density can be increased by increasing the number of semiconductor elements mounted on the module or reducing the volume of the module. To improve these two parameters, it is required to mount multiple semiconductor elements on the ceramic metal circuit board.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2017 / 056360

[0007] Patent Document 2: International Publication No. 2018 / 199060 Summary of the invention

[0008] Problems to be solved by the invention

[0009] Generally speaking, the conductivity of oxygen-free copper is about 101% IACS. However, there are local variations in conductivity in the copper plate. The variations in conductivity have adverse effects on resistance and heat dissipation.

[0010] The cause was investigated and it was found that the cause was the amount of tin (Sn) or indium (In) diffused into the copper plate. In both Patent Documents 1 and 2, an active metal bonding method is used. In the active metal bonding method, an active metal brazing material containing Ag, Cu and Ti is used. In order to improve bonding, Sn or In is added to the active metal brazing material. Sn or In has the effect of lowering the melting point of the active metal brazing material, thereby improving bonding.

[0011] For example, the active metal bonding method performs heat bonding at a high temperature in the range of 700 to 950°C. During the heat bonding process, the active metal brazing filler metal component gradually diffuses into the copper plate. The melting point of the AgCu alloy is about 780°C, while the melting point of the AgSn alloy or the AgIn alloy is about 400°C. As Sn or In diffuses into the copper plate, a large amount of the AgSn alloy or the AgIn alloy with a low melting point is formed.

[0012] An embodiment of the present invention has been made to solve such a problem, and provides a bonded body in which the generation of AgSn alloy and AgIn alloy is suppressed.

[0013] Means used to solve problems

[0014] The joint body involved in the embodiment comprises a ceramic substrate, a copper plate, and a joint layer for joining the ceramic substrate and the copper plate. The joint layer contains Ag, Cu, an active metal and a first element. The first element is one or two selected from Sn and In. When analyzing any cross section by SEM-EDX, if the place where the detected amount of Cu is more than 80% by mass and the change of the slope in the curve graph of the detected amount of Cu is the largest is taken as the first measuring point, then at the first measuring point, the detected amount of the first element (mass %) / the detected amount of Ag (mass %) is in the range of more than 0 and less than 0.4. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a diagram showing an example of a joined body according to an embodiment.

[0016] Figure 2 It is a diagram showing an example of a first measurement point and a second measurement point of a joined body according to the embodiment.

[0017] Figure 3 FIG. 1 is a diagram showing an example of a ceramic circuit board according to an embodiment.

[0018] Figure 4 FIG. 1 is a diagram showing an example of a semiconductor device according to an embodiment.

[0019] Figure 5 This is a diagram showing an example of a graph of the Cu detection amount. DETAILED DESCRIPTION

[0020] The joint body involved in the embodiment comprises a ceramic substrate, a copper plate and a joint layer for joining the ceramic substrate and the copper plate. The joint layer contains Ag, Cu, an active metal and a first element. The first element is one or two selected from Sn and In. When analyzing any cross section by SEM-EDX, if the place where the detected amount of Cu is more than 80% by mass and the change of the slope in the curve graph of the detected amount of Cu is the largest is taken as the first measuring point, then at the first measuring point, the detected amount of the first element (mass %) / the detected amount of Ag (mass %) is within the range of more than 0 and less than 0.4.

[0021] Figure 1 An example of a joined body according to the embodiment is shown. Figure 1 In the figure, reference numeral 1 is a bonded body, reference numeral 2 is a ceramic substrate, reference numeral 3 is a bonding layer, reference numeral 4 is a copper plate (front copper plate), and reference numeral 5 is a copper plate (back copper plate). Figure 1 An example is shown in which copper plates (copper plate 4, copper plate 5) are bonded to both surfaces of a ceramic substrate 2. The bonded body according to the embodiment may also be bonded to a copper plate only on one surface of the ceramic substrate 2. In addition, the number of copper plates bonded to one surface may be one or more. The copper plate 4 bonded to the surface is sometimes referred to as a surface copper plate. The copper plate 5 bonded to the back side is sometimes referred to as a back copper plate.

[0022] In the joint body 1, a ceramic substrate 2 and a copper plate 4 are joined via a joining layer 3. The joining layer 3 contains Ag, Cu, an active metal and a first element. The first element is one or two selected from Sn or In. The active metal is one or more selected from Ti (titanium), Zr (zirconium) and Hf (hafnium). The joining method using active metals is called an active metal joining method. That is, the joint body involved in the embodiment is a joint body made by the active metal joining method.

[0023] Scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX) is used to analyze any cross section of the joint body. At this time, the place where the detected amount (concentration) of Cu is 80% by mass or more and the slope in the curve diagram (distribution diagram) of the detected amount of Cu is the largest is taken as the first measurement point. In this case, in the joint body 1 involved in the embodiment, at the first measurement point, the detected amount (mass %) of the first element / the detected amount (mass %) of Ag is in the range of 0.05 or more and 0.4 or less.

[0024] First, the calculation method of the first measuring point is described. SEM-EDX is used in the measurement. A cross section is used in the analysis of SEM-EDX. The cross section is a surface that cuts the joint body 1 along a direction perpendicular to the surface of the ceramic substrate 2. The cross section to be measured is mirror-polished. As SEM-EDX, JSM-7200F manufactured by JEOL or a device having equivalent or higher performance is used. Regarding the measurement conditions, the acceleration voltage is set to 15 kV, the magnification is set to 500 times, and the counting rate is set to 10000 cps or more. For the measurement results, corrections based on the ZAF method are applied. JSM-7200F is a field emission scanning electron microscope (FE-SEM). By adopting FE-SEM, the measurement accuracy can be improved. FE-SEM is used in the measurement.

[0025] The count rate is the number of X-rays that enter the detector or are counted in one second. The unit cps is short for counts per second. The ZAF method is a method of correcting the characteristic X-ray intensity by three effects during quantitative analysis: (1) atomic number (Z) effect, (2) absorption (A) effect, and (3) fluorescence (F) effect. As long as a program for executing the ZAF method is installed in the SEM-EDX device, the measurement results can be corrected using the program.

[0026] An example of a method for specifying the first measurement point will be described with reference to copper plate 4 (front copper plate). By replacing "copper plate 4" with "copper plate 5" in the following description, the first measurement point on copper plate 5 (back copper plate) can be specified in the same manner.

[0027] The size of the measurement area of ​​SEM-EDX is set to 280μm long × 2.5μm thick, and the cross section is regionally analyzed. Regional analysis is performed from the interface between the ceramic substrate 2 and the bonding layer 3 toward the surface of the copper plate 4. The measurement area (280μm long × 2.5μm thick) is set in a non-overlapping manner. In each regional analysis, the detection amount of each element is measured. Based on the detection amount of Cu obtained by regional analysis, a curve graph of the detection amount (concentration) of Cu is prepared. In the curve graph of the detection amount of Cu, the place where the detection amount is more than 80% by mass and the change in slope is the largest is taken as the "first measurement point". Furthermore, the rough position of the interface between the ceramic substrate 2 and the bonding layer 3 can be identified based on the difference in contrast in the SEM image.

[0028] The horizontal axis of the Cu graph is the distance (μm) from the interface between the ceramic substrate 2 and the bonding layer 3. The point where the detected amount of Cu is 0 mass % is regarded as the interface between the ceramic substrate 2 and the bonding layer 3. The vertical axis of the Cu graph is the mass % (wt %) of Cu.

[0029] In addition, the preparation of the curve graph of Cu is carried out according to the following steps. First, the detection amount of each measurement area obtained by SEM-EDX is depicted to make a distribution graph. Then, a curve graph is made by connecting the points depicted in the distribution graph with smooth lines. In the preparation of the distribution graph and the smooth line, the function of the cumulative software is adopted. As the cumulative software, Excel (registered trademark) of Microsoft Corporation is adopted.

[0030] The place where the slope changes the most can be identified by the second-order differential of the Cu curve. That is, initially, the region where the detection amount of Cu is 80% by mass or more is identified from the Cu curve. Then, in the identified region, the second-order differential of the Cu curve is calculated. The minimum value is identified from the value obtained by the second-order differential. The point where the minimum value is obtained is the place where the slope changes the most, which is the first measurement point.

[0031] At the first measurement point, the mass % of components other than Cu is also analyzed. In the joint body 1 according to the embodiment, the joint layer 3 contains Ag, Cu, an active metal, and a first element. Therefore, at the first measurement point, in addition to Cu, analysis is also performed on Ag, an active metal, and a first element.

[0032] When making a curve chart of Cu, it is effective to conduct a qualitative analysis of the bonding layer 3 in advance. As a result of the qualitative analysis, the total mass of the metal components is set to 100 mass % and the mass % of Cu is calculated. As an example, by the qualitative analysis of the bonding layer 3, Ag (silver), Cu (copper), Sn (tin), Ti (titanium), Si (silicon), O (oxygen), N (nitrogen), and C (carbon) can be detected from the bonding layer 3. In this case, the metal components are Ag, Cu, Sn, and Ti. The total of these elements is set to 100 mass %, and the Cu concentration is detected. In other words, Si (silicon), O (oxygen), N (nitrogen), and C (carbon) are not counted in the metal components. The metal component is converted to the metal element single substance when it is detected as an alloy or a compound. In other words, when detecting the AgCu alloy, the AgCu alloy is counted in the Ag amount, and is also counted in the Cu amount. As long as the analysis using EDX is used, the detection amount converted to the metal element single substance can be determined. In the quantitative analysis using EDX, the measurement results of non-metallic elements are prone to deviation. Therefore, the method of counting only metal elements is preferred. In other words, the curve diagram of the detection amount (concentration) of Cu can be prepared by setting the total of the metal components to 100 mass%.

[0033] Figure 5 An example of a graph showing the amount of Cu detected. Figure 5 In the graph shown, the horizontal axis represents the distance from the interface of the ceramic substrate 2 and the bonding layer 3. The vertical axis represents the detected amount of Cu (mass %). The place where the detected amount of Cu is 0 mass % is regarded as the interface of the ceramic substrate 2 and the bonding layer 3. The slope of the graph can be calculated by software that performs second-order differentials. In the case of software included in the SEM-EDX device, the software is used to perform second-order differentials.

[0034] exist Figure 5 In the example shown, the amount of Cu detected increases from the interface between the ceramic substrate 2 and the bonding layer 3 toward the copper plate 4. At a point with a distance of about 19.5 μm, the amount of Cu detected exceeds 80% by mass. Moreover, at a point with a distance of 20 μm, the rate of increase in the amount of detection decreases. That is, in the graph, there is a point where the slope changes. When performing a second-order differential, a minimum value can be obtained at this point of change. The point where the slope changes is the first measurement point.

[0035] Here, the region from the interface between the ceramic substrate 2 and the bonding layer 3 to the first measurement point is referred to as the "first region". The region on the opposite side of the first region with respect to the first measurement point is referred to as the "second region". In addition, the slope of the amount of Cu detected in the first region is referred to as "slope A". The slope of the amount of Cu detected in the second region is referred to as "slope B". The ratio of slope B to slope A is preferably 0.5 or less.

[0036] exist Figure 5 In the curve graph shown, the ratio of the slope B of the detected amount of Cu in the second region to the slope A of the detected amount of Cu in the first region is 0.26. The so-called slope B / slope A is below 0.5, indicating that there is a change point where the Ag diffusion amount decreases. It is believed that the change point where the Ag diffusion amount decreases is the boundary between the bonding layer 3 and the copper plate 4. The so-called change point where the slope B / slope A is below 0.5 indicates that the diffusion amount of Ag into the copper plate 4 is suppressed. When the change point where the slope B / slope A is below 0.5 does not exist, it means that the diffusion amount of Ag into the copper plate is large.

[0037] The joint body 1 according to the embodiment is characterized in that, at the first measurement point, the detected amount (mass %) of the first element / the detected amount (mass %) of Ag is within a range of 0 to 0.4. This means that the amount of Sn or In is smaller than the amount of Ag at the first measurement point.

[0038] If Sn or In reacts with Ag, an AgSn alloy or AgIn is formed. The more Sn contained in the AgSn alloy increases, the lower the melting point. For example, the melting point of the solid solution of AgSn is in the range of 200°C to 500°C. The AgIn alloy also has the same tendency. The melting point of the CuSn alloy is 400°C to 700°C, and the more Sn contained in the alloy, the lower the melting point. The CuIn alloy also has the same tendency. On the other hand, the melting point of the AgCu eutectic is about 780°C.

[0039] At the first measurement point, the detected amount (mass %) of the first element / the detected amount (mass %) of Ag is greater than 0 and less than 0.4, which indicates that the diffusion amount of the first element into the copper plate 4 is suppressed. If the detected amount (mass %) of the first element / the detected amount (mass %) of Ag is greater than 0.4, an alloy with low conductivity is formed. If an alloy with low conductivity is formed, the conductivity of the copper plate 4 decreases.

[0040] In JIS-H-3100 (ISO1337, etc.), the conductivity of oxygen-free copper is specified to be 98% IACS or more. In contrast, the conductivity of Sn is about 15% IACS, and the conductivity of In is about 20% IACS. If the diffusion amount of the first element into the copper plate 4 increases, a portion with low conductivity is formed in the copper plate 4. When the detection amount (mass %) of the first element / the detection amount (mass %) of Ag exceeds 0.4, the diffusion amount of the first element into the copper plate 4 is large, and the conductivity of the copper plate 4 is reduced by more than 10%.

[0041] The ratio of the detected amount (mass %) of the first element / the detected amount (mass %) of Ag is 0, which means that the first element is below the detection limit. If the detected amount (mass %) of the first element / the detected amount (mass %) of Ag is less than 0.05 (including 0), an alloy with low conductivity will not be formed. On the other hand, the components of the bonding layer 3 will not diffuse into the copper plate, and there is a possibility that the bonding strength is insufficient.

[0042] By controlling the detected amount (mass %) of the first element / the detected amount (mass %) of Ag, it is possible to achieve both suppression of the decrease in the conductivity of the copper plate 4 and improvement in the bonding strength. Therefore, the detected amount (mass %) of the first element / the detected amount (mass %) of Ag is preferably greater than 0 and less than 0.4, and more preferably greater than 0.05 and less than 0.2. Furthermore, when both Sn and In are detected at the first measurement point, the total detected amount (mass %) of Sn and In / the detected amount (mass %) of Ag is preferably within the range of greater than 0.05 and less than 0.4.

[0043] In the joint body 1 involved in the embodiment, the detected amount (mass %) of the first element / the detected amount (mass %) of Ag is within the range of 0 to 0.4 at any first measuring point. That is, in one cross section, when two or more ranges whose positions in the in-plane direction are analyzed by SEM-EDX, the detected amount (mass %) of the first element / the detected amount (mass %) of Ag is within the range of 0 to 0.4 at the first measuring point at any range.

[0044] In addition, the first measurement point is substantially located at the boundary between the bonding layer 3 and the copper plate 4 (or the copper plate 5). The bonding layer 3 contains Cu, Ag, the first element, etc. These components gradually diffuse into the copper plate 4 with the boundary between the bonding layer 3 and the copper plate 4 as the starting point during the bonding process. The amount of the first element is reduced at the first measurement point, which means that the diffusion amount of the first element into the copper plate 4 is also suppressed.

[0045] In the first measuring point, the detected amount of Ag is preferably within the range of 3 mass % or more and less than 20 mass %. The diffusion of Ag from the bonding layer 3 to the copper plate 4 is effective for improving the bonding strength. On the other hand, if Ag diffuses too much into the copper plate 4, there is a possibility of causing the migration of Ag ions. The detected amount of Ag in the first measuring point is 3 mass % or more and less than 20 mass %, which means that while suppressing the excessive diffusion of Ag into the copper plate 4, there is also Ag necessary for the bonding of the bonding layer 3 and the copper plate 4 in the boundary. Therefore, the detected amount of Ag in the first measuring point is preferably 3 mass % or more and less than 20 mass %.

[0046] In the first measuring point, the detected amount of active metal (mass %) / the detected amount of Ag (mass %) is preferably within a range of greater than 0 and less than 0.1. The active metal can improve the bonding strength by reacting with the ceramic substrate. For example, when Ti is used as the active metal and a silicon nitride substrate is used as the ceramic substrate, a titanium nitride (TiN) layer can be formed by the reaction of Ti and the silicon nitride substrate. In the first measuring point, when the detected amount of active metal (mass %) / the detected amount of Ag (mass %) exceeds 0.1, it means that there is a large amount of active metal that does not react with the ceramic substrate 2. By setting the detected amount of active metal (mass %) / the detected amount of Ag (mass %) at the first measuring point to less than 0.1, the active metal that contributes to the reaction with the ceramic substrate 2 can be increased.

[0047] A point offset 10 μm from the first measurement point toward the surface of the copper plate 4 is defined as a “second measurement point.” In this case, the ratio of the detected amount of Ag at the second measurement point (mass %) to the detected amount of Ag at the first measurement point is preferably within a range of 0.1 to 0.7.

[0048] Figure 2 A conceptual diagram of the first measurement point and the second measurement point is shown in FIG. Figure 2 In the figure, symbol 3 is the bonding layer, symbol 4 is the copper plate, symbol 6 is the first measurement point, and symbol 7 is the second measurement point. The second measurement point is the point that is offset 10 μm from the first measurement point toward the surface of the copper plate 4 in the measurement area (length 280 μm×thickness 2.5 μm). The second measurement point is set so that the distance from the midpoint of the measurement area of ​​the first measurement point in the thickness direction to the midpoint of the measurement area of ​​the second measurement point in the thickness direction reaches 10 μm.

[0049] The ratio of the detected amount of Ag at the second measurement point (mass %) to the detected amount of Ag at the first measurement point is within the range of 0.1 to 0.7, indicating that the diffusion amount of Ag to the surface of the copper plate 4 is reduced. In other words, the diffusion amount of Ag is reduced in a short distance of 10 μm.

[0050] At the second measurement point, the detected amount (mass %) of the first element / the detected amount (mass %) of Ag is preferably within a range of 0 to 0.1. By reducing the diffusion amount of the first element at the second measurement point, the amount of alloy with low conductivity formed in the copper plate 4 can be reduced.

[0051] At the second measuring point, the detected amount of active metal (mass %) / detected amount of Ag (mass %) is preferably within a range of 0 to 0.1. By reducing the diffusion amount of active metal at the second measuring point, the active metal that contributes to the reaction between the ceramic substrate 2 and the bonding layer 3 can be increased.

[0052] Preferably, the Ag diffusion region exists between the ceramic substrate 2 and a point offset by 30 μm from the first measurement point toward the surface of the copper plate 4. In other words, preferably, there is no Ag diffusion region in the region more than 30 μm away from the first measurement point toward the surface of the copper plate 4. The so-called Ag diffusion region is a collection of measurement regions (length 280 μm × thickness 2.5 μm) where more than 0.01 mass % of Ag is detected. The detected amount of Ag less than 0.01 mass % is below the detection limit (including 0 mass %). By reducing the Ag diffusion region, the migration of Ag ions can be suppressed.

[0053] If Ag diffuses from the bonding layer 3 to the surface of the copper plate 4, Ag is precipitated on the surface of the copper plate 4. The so-called Ag ion migration refers to the phenomenon that the Ag precipitated on the surface of the copper plate 4 moves by ionization. The moved Ag is precipitated elsewhere. This becomes the cause of poor insulation. Ag ion migration is easily generated when a voltage is applied to the bonding body in an environment with high humidity. By reducing the diffusion area of ​​Ag into the copper plate 4, the diffusion of Ag near the surface of the copper plate 4 can be suppressed. As a result, Ag can be eliminated from the surface of the copper plate 4. As a result, the occurrence of Ag ion migration can be suppressed. In addition, by reducing the diffusion amount of Sn or In, the migration of Sn or In can also be suppressed.

[0054] Various components can be applied to the ceramic substrate 2. As the ceramic substrate, silicon nitride substrates, aluminum nitride substrates, aluminum oxide substrates, zirconium oxide substrates and alusil high silicon heat-resistant aluminum alloy substrates can be listed. The so-called alusil high silicon heat-resistant aluminum alloy substrate is a ceramic sintered body mixed with aluminum oxide and zirconium oxide. The thickness of the ceramic substrate 2 is preferably within a range of 0.2 mm or more and 3 mm or less.

[0055] The three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more. The thermal conductivity of the silicon nitride substrate is preferably 80 W / m·K or more. By increasing the strength of the silicon nitride substrate, the substrate can be thinned. Therefore, the three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more, more preferably 700 MPa or more. The thickness of the silicon nitride substrate can be thinned to less than 2 mm, and further thinned to less than 0.40 mm.

[0056] The three-point bending strength of the aluminum nitride substrate is in the range of 300 to 450 MPa. On the other hand, the thermal conductivity of the aluminum nitride substrate is above 160 W / m·K. Since the strength of the aluminum nitride substrate is low, the thickness of the substrate is preferably above 0.60 mm. Although the three-point bending strength of the alumina substrate is in the range of 300 to 450 MPa, the alumina substrate is relatively cheap. Although the three-point bending strength of the alusil high silicon heat-resistant aluminum alloy substrate is as high as about 550 MPa, the thermal conductivity of the alusil high silicon heat-resistant aluminum alloy substrate is in the range of 30 to 50 W / m·K.

[0057] A silicon nitride substrate is preferably used as the ceramic substrate 2. The silicon nitride substrate has high strength and can withstand the thermal shrinkage of the molding resin. In addition, by using a silicon nitride substrate having a thermal conductivity of 80 W / m·K or more, heat dissipation can be improved.

[0058] Silicon nitride substrates and aluminum nitride substrates are called nitride-based ceramic substrates. When the nitride-based ceramic and the copper plate 4 are bonded by an active metal bonding method, the active metal and the nitride-based ceramic substrate react to form an active metal nitride layer in the bonding layer 3. When Ti is used as the active metal, a titanium nitride (TiN) layer is formed. By forming such an active metal nitride layer, the bonding strength can be improved.

[0059] Alumina substrates, zirconium oxide substrates and alusil high silicon heat-resistant aluminum alloy substrates are called oxide ceramic substrates. If the oxide ceramic substrate and the copper plate 4 are joined by an active metal joining method, the active metal and the oxide ceramic substrate react to form an active metal oxide layer. When Ti is used as the active metal, a titanium oxide (TiO2) layer is formed. By forming such an active metal oxide layer, the joining strength can be improved.

[0060] The thickness of the copper plate 4 is preferably 0.3 mm or more. By thickening the copper plate 4, the heat dissipation can be improved. The current carrying capacity of the copper plate 4 can be increased. Therefore, the thickness of the copper plate 4 is preferably 0.3 mm or more, and more preferably 0.6 mm or more. There is no particular upper limit to the thickness of the copper plate, but it is preferably 5 mm or less. If it exceeds 5 mm, it is possible that it becomes difficult to form a circuit on the copper plate 4 by etching. In addition, the thickness of each of the surface copper plate and the back copper plate is preferably 0.3 mm or more.

[0061] A copper alloy plate may also be used as the copper plate. The copper plate is preferably an oxygen-free copper plate. Oxygen-free copper has a copper purity of 99.96 wt % or more as defined in JIS-H-3100. JIS-H-3100 corresponds to ISO1337 and the like.

[0062] The above-described bonded body can be applied to a ceramic circuit substrate. In addition, the ceramic circuit substrate can be applied to a semiconductor device having a semiconductor element mounted thereon.

[0063] Figure 3 An example of the ceramic circuit board according to the embodiment is shown. Figure 4 An example of a semiconductor device according to an embodiment is shown. Figure 3 and Figure 4 In the figure, reference numeral 4a denotes a copper circuit, reference numeral 8 denotes a semiconductor element, reference numeral 10 denotes a ceramic circuit substrate, and reference numeral 20 denotes a semiconductor device.

[0064] The ceramic circuit board 10 can be manufactured by providing a circuit shape to the copper plate 4 of the bonded body 1. The circuit shape is provided by using an etching process or the like. Figure 3 The example in which a copper circuit 4a is provided on the surface side of the ceramic substrate 2 and a back copper plate 5 is used as a heat sink is shown. Figure 1The front copper plate 4 shown is given a circuit shape, thereby forming one or more copper circuits 4a. In the ceramic circuit substrate 10 involved in the embodiment, the front copper plate 4 and the back copper plate 5 may both be given a circuit shape. Figure 3 An example in which two copper circuits 4 a are provided is shown. A desired number of copper circuits 4 a can be provided on the ceramic circuit substrate 10 .

[0065] In the semiconductor device 20 , the semiconductor element 8 is mounted on the ceramic circuit substrate 10 . Figure 4 An example in which one semiconductor element 8 is mounted is shown. The structure of the semiconductor device 20 according to the embodiment is not limited to the example shown in the figure, and a plurality of semiconductor elements 8 may be mounted. A plurality of semiconductor elements 8 may be mounted on one copper circuit 4a. A lead frame, bonding wire, terminal, etc. not shown in the figure may be bonded to the copper circuit 4a. In addition, a molded resin covering the semiconductor element 8 may be provided as required.

[0066] A method for producing the bonded body 1 according to the embodiment will be described. The method for producing the bonded body 1 according to the embodiment is not limited as long as it has the above-mentioned configuration. Here, a method for producing the bonded body 1 with a high yield will be described.

[0067] First, a ceramic substrate 2 is prepared. The ceramic substrate 2 is preferably one selected from a silicon nitride substrate, an aluminum nitride substrate, an aluminum oxide substrate, a zirconium oxide substrate, and an alusil substrate. In addition, a copper plate 4 is prepared.

[0068] Next, prepare an active metal brazing filler metal. First, prepare powders of the components constituting the active metal brazing filler metal. The active metal is one or more selected from Ti, Zr and Hf. As the active metal, one or two selected from metal elements of the active metal and hydrides of the active metal can be used. For example, when the active metal is Ti, use Ti powder or titanium hydride (TiH2) powder. In addition, prepare Ag powder, Cu powder and powder of the first element.

[0069] The ratio of Ag is preferably in the range of 40 mass % or more and 95 mass % or less. The ratio of Cu is preferably in the range of 3 mass % or more and 50 mass % or less. The total ratio of active metal and active metal hydride is preferably in the range of 1 mass % or more and 15 mass % or less. The total ratio of Sn and In is preferably in the range of 1 mass % or more and 30 mass % or less.

[0070] Ag and Cu are elements that constitute the main components of the bonding layer 3. The active metal or active metal hydride is a component that can achieve strong bonding by reacting with the ceramic substrate 2. Sn or In has the effect of lowering the melting point of the active metal brazing filler metal.

[0071] In the active metal brazing filler metal, carbon (C) may be added in an amount of 0.1% to 2% by mass. In the active metal brazing filler metal, one or more selected from tungsten (W), molybdenum (Mo) and rhenium (Re) may be added in an amount of 0.1% to 10% by mass. By adding carbon, tungsten, molybdenum or rhenium, the fluidity of the active metal brazing filler metal can be controlled. Magnesium (Mg) may also be added to the active metal brazing filler metal.

[0072] The above-mentioned active metal brazing filler metal component ratio is a ratio when the total of each metal component is set to 100 mass%. For example, when titanium nitride powder is used, the mass % of titanium nitride can be controlled within the above-mentioned range. The mass of organic matter such as a binder is not counted. The active metal brazing filler metal paste is prepared by mixing each brazing filler metal component and adding a binder etc.

[0073] Next, a laminate including a ceramic substrate 2, an active metal brazing paste layer and a copper plate 4 is prepared. The active metal brazing paste is applied on the ceramic substrate 2, and the copper plate 4 is arranged thereon. The active metal brazing paste can also be applied on both sides of the ceramic substrate 2, and the copper plates 4 can be arranged on both sides respectively. Alternatively, the active metal brazing paste can also be applied on the copper plate 4, and the ceramic substrate 2 can be arranged thereon. The number of stacking of the ceramic substrate 2 and the copper plate 4 can be increased as needed. For example, the number of stacking can also be increased in the manner of copper plate / active metal brazing paste layer / ceramic substrate / active metal brazing paste layer / copper plate / active metal brazing paste layer / ceramic substrate / active metal brazing paste layer / copper plate. Through this process, a laminate having a ceramic substrate 2, an active metal brazing paste layer and a copper plate 4 can be prepared.

[0074] Next, a heating and joining process is performed. The joining temperature is preferably in the range of 700°C to 950°C. The joining temperature is a temperature maintained for more than a specified time. When using the above-mentioned active metal brazing material, the ceramic substrate 2 and the copper plate 4 can be joined in the range of 700°C to 950°C. Therefore, the joining temperature is set in the range of 700°C to 950°C. If the joining temperature is lower than 700°C, there is a possibility that the joining strength is insufficient. If the joining temperature is higher than 950°C, there is a possibility that the diffusion amount of Ag, active metal or first element into the copper plate 4 increases. Therefore, the joining temperature is preferably in the range of 700°C to 950°C, and more preferably in the range of 850°C to 920°C.

[0075] In addition, the holding time of the bonding temperature is preferably within a range of 3 minutes to 60 minutes. If the temperature deviation in the furnace is taken into account, the time for holding the laminate in a temperature zone within the range of ±30°C of the bonding temperature is counted as the holding time of the bonding temperature. For example, when the bonding temperature is 880°C, the time for holding the laminate in a temperature zone of 880°C ±30°C is the holding time of the bonding temperature.

[0076] If the holding time of the bonding temperature is less than 3 minutes, there is a possibility that the bonding strength is insufficient. If the holding time of the bonding temperature is longer than 60 minutes, the time of exposure to high temperature is extended. There is a possibility that the diffusion amount of Ag, active metal or the first element into the copper plate 4 increases. Therefore, the holding time of the bonding temperature is preferably within the range of more than 3 minutes and less than 60 minutes, and more preferably within the range of more than 5 minutes and less than 40 minutes.

[0077] It is preferred to use a continuous furnace in the heat bonding process. By using a continuous furnace, the laminate can be bonded in a nitrogen atmosphere. The so-called nitrogen atmosphere refers to an atmosphere in which nitrogen is greater than 98 vol% and less than 100 vol%. In a continuous furnace, the laminate can be heat-bonded while conveying items by a conveyor belt or the like. By using a continuous furnace, the heating time from room temperature to the bonding temperature and the cooling time from the bonding temperature to room temperature can be shortened. As a result, the time the laminate is exposed to high temperature can be shortened more than necessary.

[0078] For example, in the previous active metal bonding method, the laminate is heated and bonded in a vacuum. An intermittent furnace is used for bonding in a vacuum. In the intermittent furnace, the laminate is placed in a closed space and heated. When an intermittent furnace is used, the heating and cooling of the heat capacity of the furnace body (closed space) itself takes time. Therefore, it is necessary to adjust the temperature of the furnace body, and the heating process and the cooling process take time. The heating rate and the cooling rate of the intermittent furnace are in the range of 1 to 3°C / minute. In the intermittent furnace, after being maintained at the bonding temperature, it takes a long time to return to room temperature. Therefore, the bonded body is exposed to high temperature for a long time. As a result, the diffusion amount of Ag and the first element into the copper plate 4 increases. On the other hand, in a continuous furnace, since the sample passes through the furnace, the heating time can be determined only by the heat capacity of the sample itself. Therefore, the heating rate and the cooling rate can be accelerated.

[0079] When a continuous furnace is used for the heating and joining process, the active metal content of the active metal brazing filler metal is preferably 5% by mass or more. In the continuous furnace, the laminate can be joined in an inactive atmosphere. As an inactive atmosphere, a nitrogen atmosphere or an argon atmosphere can be listed. When the cost is taken into consideration, a nitrogen atmosphere can be used. On the other hand, the active metal has a high reactivity with nitrogen. By setting the content of the active metal in the active metal brazing filler metal to 5% by mass or more, the ratio of the active metal that contributes to the joining can be increased without reacting with the nitrogen atmosphere. Therefore, the yield rate when a continuous furnace is used can be improved.

[0080] When a continuous furnace is used, the heating rate of the laminate and the cooling rate of the joint body can be made above 15°C / min. By accelerating the heating rate and the cooling rate, the time for which the laminate or the joint body is exposed to high temperature can be shortened. Furthermore, the upper limit of the heating rate and the cooling rate is not particularly limited, but is preferably below 100°C / min. If it exceeds 100°C / min, there is a possibility that the joint body is deformed due to excessive temperature changes.

[0081] The difference between the heating rate and the cooling rate is preferably less than 20°C / minute. The difference between the heating rate and the cooling rate can be expressed by |heating rate-cooling rate|. That is, preferably |heating rate-cooling rate|≤20°C / minute. By reducing the difference between the heating rate and the cooling rate, the diffusion amount of the active metal brazing component can be uniformed. Thus, no matter which first measuring point of the joint 1 is measured, the detection amount (mass %) of the first element / the detection amount (mass %) of Ag can be within the range of more than 0 and less than 0.4.

[0082] In the temperature distribution diagram of the heating and bonding process, the temperature of the stack is used. For measuring the temperature of the stack, a method of installing a thermocouple on the stack and passing it through a continuous furnace is effective. A heating process, a heating and bonding process, and a cooling process are performed, and the temperature distribution diagram of the stack is measured. From the temperature distribution diagram, the heating rate, the holding time of the bonding temperature, and the cooling rate are calculated. Here, the heating rate is the average heating rate from 200°C to the bonding temperature. The cooling rate is the average cooling rate from the bonding temperature to 200°C.

[0083] The space for the temperature raising process may also be divided into a plurality of zones. For example, the plurality of zones include a normal temperature zone, a zone from normal temperature to 200°C, a zone from 200°C to 400°C, a zone from 400°C to 600°C, a zone from 600°C to the bonding temperature, and a zone for maintaining the laminate at the bonding temperature. The laminate is heated in each zone in turn. The temperature raising process is performed by the laminate passing through a plurality of zones.

[0084] In the heating process, in the initial zone where the stack is heated, the temperature of the stack is preferably within the range of 150°C to 400°C. The so-called initial treatment zone is the zone where the stack is initially heated in the continuous furnace. In the manufacturing method of the joint body involved in the embodiment, the heating rate from 200°C to the joining temperature is controlled in the heating process. In the initial treatment zone, by making the temperature of the stack in the range of 150°C to 400°C in advance, it becomes easy to control the heating rate from 200°C. Therefore, in the initial treatment zone, the temperature of the stack is preferably within the range of 150°C to 400°C, and more preferably within the range of 180°C to 370°C. In addition, if it is in this temperature range, the effect of degreasing the binder in the solder paste can also be obtained. Removal of the binder is effective in inhibiting the diffusion of active metal solder components into the copper plate 4.

[0085] The average conveying speed of the stack is preferably more than 1 cm / minute. The so-called average conveying speed is the average value of the moving speed of the stack when conveying in the heating process, the heating bonding process, and the cooling process. If the average conveying speed is lower than 1 cm / minute, there is a possibility that the mass productivity is reduced due to the slow conveying speed. Furthermore, when the process of stopping the conveying is included, the conveying speed in the process is counted as 0 cm / minute. For example, when conveying at a conveying speed of 5 cm / minute for 30 minutes and conveying at a conveying speed of 10 cm / minute for 10 minutes, the average conveying speed is 6.3 cm / minute. When conveying at a conveying speed of 5 cm / minute for 60 minutes and stopping the conveying for 30 minutes, the average conveying speed is 3.3 cm / minute.

[0086] The upper limit of the average transmission speed is not particularly limited, but is preferably less than 30 cm / minute. If the average transmission speed is fast, the transmission distance required for heating, heating bonding and cooling is extended, and there is a possibility of causing large-scale manufacturing equipment. In addition, if the average transmission speed is fast, there is a possibility that the heat transfer to the stack becomes uneven. Therefore, the average transmission speed is preferably within the range of more than 1 cm / minute and less than 30 cm / minute, and more preferably within the range of more than 8 cm / minute and less than 20 cm / minute. If within this range, on the basis of making the heat transfer to the stack uniform, it is also possible to improve mass production.

[0087] Through the above steps, the assembly 1 can be manufactured. Next, a step of giving a circuit shape to the copper plate 4 is performed. As for giving the circuit shape, a method of performing an etching step on the copper plate 4 is effective. Through the etching step, the copper plate 4 can be processed into a copper circuit 4a. By giving a circuit shape to the copper plate 4 of the assembly 1, a ceramic circuit substrate 10 can be obtained. Alternatively, the copper circuit 4a can also be manufactured by processing the copper plate 4 into a circuit shape in advance. By joining the copper circuit 4a to the ceramic substrate 2, a ceramic circuit substrate 10 can be obtained. It is also possible to manufacture a large assembly and process multiple pieces simultaneously. That is, one assembly can also be divided into a plurality of assemblies 1. In addition, by mounting a semiconductor element 8 on the obtained ceramic circuit substrate 10, a semiconductor device 20 can be manufactured.

[0088] (Example)

[0089] (Examples 1 to 8, Comparative Examples 1 to 2)

[0090] As ceramic substrates, silicon nitride substrates, aluminum nitride substrates, and aluminum oxide substrates were prepared. The thermal conductivity of the silicon nitride substrate was 90 W / m·K, and the three-point bending strength was 650 MPa. The thermal conductivity of the aluminum nitride substrate was 170 W / m·K, and the three-point bending strength was 400 MPa. The thermal conductivity of the aluminum oxide substrate was 20 W / m·K, and the three-point bending strength was 430 MPa. The longitudinal length, lateral length, and thickness of each substrate are shown in Table 1.

[0091] Table 1

[0092] Ceramic Substrate Length × width × thickness (mm) Silicon nitride based 190×140×0.32 Aluminum Nitride Substrate 100×100×0.635 Alumina substrate 200×180×0.635

[0093] Next, active metal brazing filler metals were prepared as shown in Table 2. In Table 2, the composition of the active metal brazing filler metals is described with the total of the brazing filler metal components being 100% by mass.

[0094] Table 2

[0095] Brazing material layer Active metal brazing filler metal composition (wt%) Brazing material 1 <![CDATA[Ag(40.9)、Cu(35.3)、Sn(15)、TiH2(8.7)、C(0.1)]]> Brazing material 2 <![CDATA[Ag(65)、Cu(20)、Sn(10)、TiH2(5)]]> Brazing material 3 <![CDATA[Ag(90)、Cu(4)、Sn(4)、TiH2(2)]]> Brazing material 4 <![CDATA[Ag(54.8)、Cu(25)、Sn(10)、TiH2(10)、C(0.2)]]> Brazing material 5 <![CDATA[Ag(41)、Cu(22)、Sn(25)、TiH2(12)]]>

[0096] Next, a copper plate was prepared. Oxygen-free copper was used as the copper plate. The thickness of the copper plate is shown in Table 3.

[0097] Table 3

[0098] Thickness(mm) Copper Plate 1 0.3 Copper Plate 2 0.8

[0099] An active metal brazing material is added with a binder and the like to prepare an active metal brazing material paste. The active metal brazing material paste is applied on a ceramic substrate. A copper plate is arranged on the ceramic substrate to produce a laminate. In the laminate, copper plates are arranged on both sides of the ceramic substrate via the active metal brazing material paste. The combination of the ceramic substrate, active metal brazing material and copper plate in each laminate is shown in Table 4.

[0100] Table 4

[0101] Ceramic Substrate Active metal brazing filler metal Copper Plate Laminated body 1 Silicon Nitride Substrate Brazing material 1 Copper Plate 2 Laminated body 2 Silicon Nitride Substrate Brazing material 3 Copper Plate 2 Laminated body 3 Aluminum Nitride Substrate Brazing material 2 Copper Plate 1 Laminated body 4 Alumina substrate Brazing material 2 Copper Plate 1 Laminated body 5 Silicon Nitride Substrate Brazing material 4 Copper Plate 1 Laminated body 6 Silicon Nitride Substrate Brazing material 4 Copper Plate 2 Laminated body 7 Silicon Nitride Substrate Brazing material 1 Copper Plate 2 Laminated body 8 Silicon Nitride Substrate Brazing material 1 Copper Plate 2 Laminated body 9 Silicon Nitride Substrate Brazing material 5 Copper Plate 2

[0102] Next, the laminate was subjected to a heat bonding step to produce a bonded body. In Examples 1 to 8 and Comparative Example 1, the heat bonding step was performed using a continuous furnace. In Comparative Example 2, the heat bonding step was performed using a vacuum batch furnace. The bonding conditions are shown in Table 5.

[0103]

[0104] In Table 5, the temperature increase rate is the average temperature increase rate from 200° C. to the bonding temperature. The temperature drop rate is the average temperature drop rate from the bonding temperature to 200° C. Through this process, a bonded body was produced.

[0105] Next, the diffusion state of the active metal brazing filler metal component in the copper plate of each joint body involved in the embodiment and the comparative example was investigated. In the measurement of the diffusion state, an arbitrary cross section of the joint body was used. Each cross section was mirror-finished to prepare a sample for measurement.

[0106] SEM-EDX was used to make a curve graph of the detected amount of Cu. As SEM-EDX, JSM-7200F was used. The measurement area was set to 280 μm long × 2.5 μm thick. Other measurement methods were as described above. The first measurement point, the second measurement point and the Ag diffusion area were obtained from the curve graph of Cu. In addition, at the first measurement point, the detected amount (concentration) of Cu was more than 80% by mass, and was specified from the minimum value in the second-order differential of the curve graph. The results are shown in Table 6.

[0107]

[0108] It can be seen from Table 6 that in the joint body involved in the embodiment, in the first measuring point, the detection amount (mass %) of the first element / the detection amount (mass %) of Ag is within the range of more than 0 and less than 0.4. The detection amount (mass %) of Ag in the second measuring point / the detection amount (mass %) of Ag in the first measuring point is within the range of more than 0.1 and less than 0.7. The Ag diffusion area is less than 30μm. The distance from the first measuring point to the second measuring point is 10μm. It is known that in such a short distance of 10μm, the diffusion amount of elements such as Ag and Sn is reduced. In addition, in the curve diagram of Cu of the joint body involved in the embodiment, the slope of the detection amount of Cu in the second area / the slope of the detection amount of Cu in the first area is less than 0.5.

[0109] In contrast, in Comparative Example 1, although a continuous furnace is used, the heating rate and the cooling rate are slow. Therefore, the heat applied to the laminate increases, and it is believed that the diffusion amount of Ag, Sn, etc. increases. In Comparative Example 2, a vacuum intermittent furnace is used. Compared with the continuous furnace, the intermittent furnace has a large heat load on the laminate, so the diffusion amount of Ag and Sn increases. In addition, in the curve diagram of Cu of the joint body involved in the comparative example, the slope of the detection amount of Cu in the second area / the slope of the detection amount of Cu in the first area are both greater than 0.5.

[0110] In Examples 1 and 3 to 9, where the amount of Ti in the active metal brazing filler metal was 5 mass % or more, the yield was good. In contrast, in Example 2, where the amount of Ti in the active metal brazing filler metal was as low as 2 mass %, the yield was slightly reduced.

[0111] Next, each bonded body according to the example and the comparative example was subjected to etching to produce a ceramic circuit board. The ceramic circuit board was subjected to a copper circuit bonding strength test, a copper circuit conductivity test, and an Ag migration test.

[0112] The bonding strength of the copper circuit was measured by a peel test. The measurement conditions of the peel test are as follows. First, a portion of the bonded copper circuit is peeled off, and a portion of about 10 mm of the peeled copper circuit is bent at a right angle relative to the ceramic substrate to make a clamping portion. Using a measuring table, the clamping portion is stretched at a certain speed (50.0 mm / min) relative to the ceramic substrate. During the stretching, the average value of the stored value of the dynamometer (spring balance) is read.

[0113] The following formula 1 shows the relationship between the peel strength δf (kgf / cm), the bond width W (mm) of the stretched copper circuit, and the measured value P (kgf). The peel strength δf of formula 1 is converted into the peel strength F (N / m) in SI units by formula 2. The average value read from the dynamometer is converted into the peel strength by the following formula 2.

[0114] δf=(10 / W)×P (1)

[0115] F=δf×9.8×10 2 (2)

[0116] Regarding the conductivity of the copper circuit, the resistance value was measured using a tester. When the resistance value of the oxygen-free copper plate before bonding was set to 100, the ceramic circuit substrate with a copper circuit resistance value of 90 or more was evaluated as "maintained", and the ceramic circuit substrate with a copper circuit resistance value of less than 90 was evaluated as "reduced". In each example and each comparative example, the resistance value of 10 points on the ceramic substrate was measured, and even if one point was less than 90, it was evaluated as "reduced".

[0117] In the evaluation of Ag migration characteristics, a voltage was applied to the ceramic circuit substrate under high temperature and high humidity conditions, and the occurrence rate of Ag migration marks was investigated. As a measuring device, an electrochemical migration evaluation system manufactured by ESPEC was used. Under an environment of temperature 85°C and humidity 85%, an external voltage of AC2000V (peak voltage 2820V) was applied to the ceramic circuit substrate for 30 consecutive hours. Then, the presence or absence of Ag migration marks on the surface of the ceramic circuit substrate was investigated. 100 ceramic circuit substrates involved in each embodiment and each comparative example were evaluated respectively. Examples in which there were more than 0 and less than 5 ceramic circuit substrates with more than one Ag migration mark were evaluated as "good". Examples in which there were more than 6 ceramic circuit substrates with more than one Ag migration mark were evaluated as "poor". The results are shown in Table 7.

[0118] Table 7

[0119]

[0120] It can be seen from Table 7 that according to the embodiment, the TCT characteristics and Ag migration characteristics are improved compared with the comparative example. In addition, the Sn migration is also suppressed in the embodiment. The bonding strength is the same between the embodiment and the comparative example, but the performance as a ceramic circuit substrate is improved by improving the TCT characteristics and Ag migration characteristics. In addition, in the ceramic circuit substrate involved in the embodiment, the decrease in the conductivity of the copper plate is suppressed.

[0121] (Composition 1)

[0122] A joint body comprising:

[0123] Ceramic substrates,

[0124] Copper plate, and

[0125] a bonding layer for bonding the ceramic substrate and the copper plate,

[0126] The bonding layer contains Ag, Cu, an active metal and a first element.

[0127] The first element is one or two selected from Sn and In,

[0128] When analyzing any cross section by SEM-EDX, when the place where the detected amount of Cu is more than 80 mass% and the slope of the curve graph of the detected amount of Cu changes the most is taken as the first measuring point, then at the first measuring point, the detected amount of the first element (mass %) / the detected amount of Ag (mass %) is within the range of more than 0 and less than 0.4.

[0129] (Composition 2)

[0130] The bonded body according to Configuration 1, wherein at the first measurement point, the ratio of the detected amount (mass %) of the first element to the detected amount (mass %) of Ag is within a range of 0.05 to 0.2.

[0131] (Composition 3)

[0132] According to the joint body described in structure 1 or 2, wherein, when the area from the interface between the ceramic substrate and the bonding layer to the first measuring point is taken as the first area, and the area on the opposite side of the first area relative to the first measuring point is taken as the second area, in the curve graph, the ratio of the slope of the detected amount of Cu in the second area to the slope of the detected amount of Cu in the first area is less than 0.5.

[0133] (Composition 4)

[0134] The bonded body according to any one of Configurations 1 to 3, wherein the amount of Ag detected at the first measurement point is within a range of 3 mass % or more and less than 20 mass %.

[0135] (Composition 5)

[0136] The bonded body according to any one of Configurations 1 to 4, wherein the ratio of the detected amount of active metal (mass %) / the detected amount of Ag (mass %) at the first measurement point is within a range of 0 to 0.1.

[0137] (Composition 6)

[0138] The bonded body according to any one of Configurations 1 to 5, wherein when a second measurement point is set at a position offset by 10 μm from the first measurement point to the surface of the copper plate,

[0139] The ratio of the detected amount of Ag at the second measurement point (mass %) to the detected amount of Ag at the first measurement point is within a range of 0.1 to 0.7.

[0140] (Composition 7)

[0141] The bonded body according to Configuration 6, wherein, at the second measurement point, the detected amount (mass %) of the first element / the detected amount (mass %) of Ag is within a range of 0 to 0.1.

[0142] (Composition 8)

[0143] The bonded body according to Configuration 6, wherein, at the second measurement point, the detected amount (mass %) of the active metal / the detected amount (mass %) of Ag is within a range of 0 to 0.1.

[0144] (Composition 9)

[0145] The bonded body according to any one of Configurations 1 to 8, wherein the Ag diffusion region exists between the ceramic substrate and a point offset by 30 μm from the first measurement point toward the surface of the copper plate.

[0146] (Composition 10)

[0147] The bonded body according to any one of Configurations 1 to 9, wherein the copper plate has a thickness of 0.3 mm or more.

[0148] (Composition 11)

[0149] The bonded body according to any one of Configurations 1 to 10, wherein the ceramic substrate is a silicon nitride substrate.

[0150] (Composition 12)

[0151] A ceramic circuit board obtained by providing a circuit shape to the copper plate constituting the bonded body according to any one of Items 1 to 11.

[0152] (Composition 13)

[0153] A semiconductor device comprising:

[0154] The ceramic circuit substrate as described in construction 12, and

[0155] A semiconductor element is mounted on the copper plate to which the circuit shape is given.

[0156] (Composition 14)

[0157] A method for producing a joined body, which is the method for producing a joined body according to any one of configurations 1 to 11, comprising:

[0158] a step of preparing a laminated body comprising the ceramic substrate, an active metal brazing filler metal having an active metal content of 5 mass % or more and 15 mass % or less, and the copper plate; and

[0159] The step of bonding the ceramic substrate and the copper plate by heating using a continuous furnace.

[0160] Several embodiments of the present invention have been described above, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the scope of the main purpose of the invention. These embodiments and their modifications are included in the scope and main purpose of the invention, and are also included in the invention recorded in the claims and their equivalents. In addition, the above-mentioned embodiments can also be implemented by combining with each other.

[0161] Explanation of symbols

[0162] 1-joint

[0163] 2-Ceramic substrate

[0164] 3-Joint layer

[0165] 4-Copper coin (copper plate)

[0166] 4a - Copper Circuit

[0167] 5-Copper plate (copper back plate)

[0168] 6-1st measuring point

[0169] 7-2nd measuring point

[0170] 8-Semiconductor components

[0171] 10-Ceramic circuit substrate

[0172] 20-Semiconductor devices

Claims

1. A conjugate comprising: Ceramic substrates, Copper plate, and a bonding layer for bonding the ceramic substrate and the copper plate, The bonding layer contains Ag, Cu, an active metal and a first element, The first element is one or two selected from Sn and In, When analyzing any cross section by SEM-EDX, when the place where the detected amount of Cu is more than 80 mass% and the slope of the curve graph of the detected amount of Cu changes the most is taken as the first measuring point, at the first measuring point, the detected amount of the first element (mass %) / the detected amount of Ag (mass %) is within the range of more than 0 and less than 0.

4.

2. The conjugate according to claim 1, wherein At the first measurement point, the ratio of the detected amount (mass %) of the first element to the detected amount (mass %) of Ag is within a range of 0.05 to 0.

2.

3. The conjugate according to claim 1 or 2, wherein: When the area from the interface between the ceramic substrate and the bonding layer to the first measuring point is taken as the first area, and the area on the opposite side of the first area relative to the first measuring point is taken as the second area, in the curve graph, the ratio of the slope of the detected amount of Cu in the second area to the slope of the detected amount of Cu in the first area is less than 0.

5.

4. The conjugate according to claim 1 or 2, wherein: The detected amount of Ag at the first measurement point is within a range of 3 mass % or more and less than 20 mass %.

5. The conjugate according to claim 1 or 2, wherein: The ratio of the detected amount of active metal (mass %) / the detected amount of Ag (mass %) at the first measurement point is within a range of 0 to 0.

1.

6. The conjugate according to claim 1 or 2, wherein: When the second measurement point is set at a position shifted by 10 μm from the first measurement point to the surface of the copper plate, The ratio of the detected amount of Ag at the second measurement point (mass %) to the detected amount of Ag at the first measurement point is within a range of 0.1 to 0.

7.

7. The conjugate according to claim 6, wherein: At the second measurement point, the detected amount (mass %) of the first element / the detected amount (mass %) of Ag is within a range of 0 to 0.

1.

8. The conjugate according to claim 6, wherein At the second measurement point, the ratio of the detected amount of active metal (mass %) to the detected amount of Ag (mass %) is within a range of 0 to 0.

1.

9. The conjugate according to claim 1 or 2, wherein: The Ag diffusion region exists between the ceramic substrate and a point offset by 30 μm from the first measurement point toward the surface of the copper plate.

10. The conjugate according to claim 1 or 2, wherein: The copper plate has a thickness of 0.3 mm or more.

11. The conjugate according to claim 1 or 2, wherein: The ceramic substrate is a silicon nitride substrate. 12 . A ceramic circuit board, wherein a circuit shape is imparted to the copper plate of the bonded body according to claim 1 .

13. A semiconductor device comprising: The ceramic circuit substrate according to claim 12, and A semiconductor element is mounted on the copper plate to which the circuit shape is given.

14. The conjugate according to claim 6, wherein The thickness of the copper plate is greater than 0.3 mm. The ceramic substrate is a silicon nitride substrate.

15. The conjugate according to claim 7, wherein: The thickness of the copper plate is greater than 0.3 mm. The ceramic substrate is a silicon nitride substrate.

16. The conjugate according to claim 6, wherein The Ag diffusion region exists between the ceramic substrate and a point offset by 30 μm from the first measurement point toward the surface of the copper plate.

17. The conjugate according to claim 7, wherein: The Ag diffusion region exists between the ceramic substrate and a point offset by 30 μm from the first measurement point toward the surface of the copper plate. 18 . A ceramic circuit board, wherein a circuit shape is imparted to the copper plate of the bonded body according to claim 14 . 19 . A ceramic circuit board, wherein a circuit shape is imparted to the copper plate of the bonded body according to claim 15 . 20 . A ceramic circuit board, wherein a circuit shape is imparted to the copper plate of the bonded body according to claim 16 .

21. A method for producing a bonded body, which is the method for producing a bonded body according to claim 1, comprising: a step of preparing a laminated body comprising the ceramic substrate, an active metal brazing filler metal having an active metal content of 5 mass % or more and 15 mass % or less, and the copper plate; and The step of bonding the ceramic substrate and the copper plate by heating using a continuous furnace.

Citation Information

Patent Citations

  • Circuit substrate and semiconductor device

    WO2017056360A1

  • Ceramic circuit board, method for manufacturing ceramic circuit board, and module using ceramic circuit board

    WO2018199060A1

  • Copper / ceramic assembly, insulation circuit board, method for manufacturing copper / ceramic assembly, and method for manufacturing insulation circuit board

    JP2021091595A

  • Ceramic Copper Circuit Board And Semiconductor Device Based On The Same

    US20190327831A1

  • Laminate, ceramic-copper circuit board, method for manufacturing laminate, and method for manufacturing ceramic-copper circuit board

    WO2021187201A1